Emancipatory Discourse and Liberation - Joseph A. Raelin (Management Learning, 2008)
This article takes up an important question that has puzzled learning theorists in the critical tradition, namely, are the dialogic practices of emancipatory discourse sufficient to change oppressive conditions in the power structure of the modern organization? In other words, can critical dialogic processes change the social order to close the gap between a privileged class of managers and workers, or do we require class struggle and structural reform? By elaborating on such methods as dialogue, public reflection and action science, this article attempts to make the case that marginalized groups in society might find their voice in projects that are intentionally contextualized and publicly reflective. These methods have found applications in some illustrated critical pedagogies, although not without strain induced from conventional institutions. The article concludes with an enumeration of some conditions under which emancipatory discourse and liberationist struggle may coincide.
Keywords: M14; M54; P11; O15; D63; B14; B24; 650; Emancipation; Liberation; Dialogue; Public reflection; Action science; Critical action learning; Critical theory; Labor process theory